A chromosome walk linking the gatA and alcC genes of Aspergillus nidulans - Robyn Lints; Michael Hynes; Meryl Davis (Fungal Genetics Reports, 1995)
The amdA gene of Aspergillus nidulans has been mapped to linkage group VII, between the gatA and alcC genes (Jones and Sealy- Lewis 1990 Curr. Genet. 17:81-85). As clones of both of the genes flanking amdA were available, they were used as starting points for chromosome walking towards amdA. The relative orientation of these genes on linkage group VII was not known at the time. Therefore, both walks extended in both directions until overlapping clones from the different walks were detected. The total distance covered by all walks is approximately 240 kb.